High-bandwidth, low-power CMOS transistor based cab for field programmable analog array - Al-Bawri, Samir Salem; Obadi, Ameen; Hossain, Kabir; Abdulhameed, Abdullah; Jusoh, Muzammil; Sabapathy, Thennarasan; El-Din Hussein, Alaa; Al Gburi, Ahmed Jamal Abdullah (Tech Science Press, 2023)
This article presents an integrated current mode configurable analog block (CAB) system for field-programmable analog array (FPAA). The proposed architecture is based on the complementary metal-oxide semiconductor (CMOS) transistor level design where MOSFET transistors operating in the saturation region are adopted. The proposed CAB architecture is designed to implement six of the widely used current mode operations in analog processing systems: addition, subtraction, integration, multiplication, division, and pass operation. The functionality of the proposed CAB is demonstrated through these six operations, where each operation is chosen based on the user’s selection in the CAB interface system. The architecture of the CAB system proposes an optimized way of designing and integrating only three functional cells with the interface circuitry to achieve the six operations. Furthermore, optimized programming and digital tuning circuitry are implemented in the architecture to control and interface with the functional cells. Moreover, these designed programming and tuning circuitries play an essential role in optimizing the performance of the proposed design. Simulation of the proposed CMOS Transistor Based CAB system is carried out using Tanner EDA Tools in 0.35 μm standard CMOS technology. The design uses a ±1.5 V power supply and results in maximum 3 dB bandwidth of 34.9 MHz and an approximate size of 0.0537 mm2. This demonstrates the advantages of the design over the current state-of-the-art designs presented for comparison in this article. Consequently, the proposed design has a clear aspect of simplicity, low power consumption, and high bandwidth operation, which makes it a suitable candidate for mobile telecommunications applications